2002
DOI: 10.1074/jbc.m200662200
|View full text |Cite
|
Sign up to set email alerts
|

A Trypanosome Mitochondrial RNA Polymerase Is Required for Transcription and Replication

Abstract: Understanding mitochondrial transcription is a requisite first step toward understanding the regulation of mitochondrial gene expression in kinetoplastids. Here we report the identification and functional characterization of a mitochondrial RNA polymerase (mtRNAP) from Trypanosoma brucei, the first trans-acting factor involved in kinetoplast mitochondrial transcription to be identified. Using sequences conserved among the catalytic domains of the single-subunit mtRNAPs, we were able to obtain a full-length seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 48 publications
3
47
0
Order By: Relevance
“…Next, we have hybridized blots containing mtRNA with a probe against cox1 mRNA. In agreement with the previous study (Grams et al 2002), this never-edited transcript is undetectable 3 d after RNAi is triggered (Fig. 6B).…”
Section: Mtrna Polymerase Appears To Transcribe Minicirclessupporting
confidence: 81%
See 3 more Smart Citations
“…Next, we have hybridized blots containing mtRNA with a probe against cox1 mRNA. In agreement with the previous study (Grams et al 2002), this never-edited transcript is undetectable 3 d after RNAi is triggered (Fig. 6B).…”
Section: Mtrna Polymerase Appears To Transcribe Minicirclessupporting
confidence: 81%
“…Englund, Johns Hopkins University), we have first verified the RNAi effect by Northern analysis, as antibodies against the T. brucei mtRNAP are not available. As shown in Figure 6A, the mtRNAP mRNA is undetectable 3 d after tetracycline induction, the time point at which growth inhibition is first observed (Grams et al 2002). Next, we have hybridized blots containing mtRNA with a probe against cox1 mRNA.…”
Section: Mtrna Polymerase Appears To Transcribe Minicirclesmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, we found that mRNA levels were reduced more than the levels of mtDNA, and this, too, may reflect a higher turnover rate for mRNAs as compared with that of mtDNA. Interestingly, a similar result was obtained in an RNA knock-down analysis of mitochondrial RNA polymerase in trypanosomes (44). In any case, because of the differential effects we observed on mtDNA copy number and transcription in the overexpression analyses of d-mtTFB2 and d-TFAM, it is apparent that the effect of d-mtTFB2 on transcription is not a simple consequence of mtDNA dose.…”
Section: Discussionsupporting
confidence: 60%